Corn gluten high level inclusion in farmed trout nutrition: productive and hematological effects and quality of product - Sicuro, Benedetto; Barbera, Salvatore; Daprà, Franco; Gai, Francesco; Macchi, Elisabetta (Progress in Nutrition, 2017)
Background and aim of the work: The substitution of fish meal in fish feeds has been thoroughly studied subject in aquaculture nutrition. Among cereals, corn gluten is one of the most used vegetal protein in fish feeds. This study investigated the effect of high level corn gluten inclusion in rainbow trout nutrition and related effects on productive and quality of product. Methods: Three isoproteic (crude protein: 41%) and isoenergetic (19 MJ kg-1 of dry matter) diets were tested with graded level of corn gluten  inclusion (40, 50 and 60%).  Four hundred eighty rainbow trout (body weight : 50.7 ± 2.0 g) were utilised. At the end of experiment, productive traits, haematological analyses and quality analysis were carried out. Results: Considering the productive traits, statistically significant differences were found between fish fed with control and corn gluten diets. In all the measured parameters a similar pattern was visible showing main difference  between highest level of corn gluten inclusion GLU50 and fish meal fed fish, CTRL (Specific Growth Rate, GLU50:1.11 ± 0.1; GLU40: 1.14 ±  0.02ab, CTRL, 1.36 ±  0.1b;Food Conversion Rate, GLU50: 2.02 ±  0.1ab; GLU40: 1.82 ± 0.1ab, CTRL: 1.5 ±  0.1b). Conclusions: Productive and haematological data indicated that the maximum corn gluten inclusion was reached with 40%. Quality of product analysis indicated that the fillets of fish fed with an inclusion of 50% of corn gluten showed similar aroma features of control fish fillet.